Performance comparison of selection combining with full CSI and switch-and-examine combining with and without post-selection - Swaminathan, Ramabadran (2017)
Selection combining (SC) with full channel state information (CS!) achieves full diversity order in a decode-and-forward (DF) relaying system. However, the estimation of CSI of all the links is a cumbersome process. As an alternative, switched-diversity techniques have been proposed in the literature, in which CSI of all the links are not simultaneously required. In this paper, we compare the variants of the switched-diversity and full-CSI SC schemes through a paired error approach for a multiDF-relaying-based cooperative diversity system. We derive the exact symbol error probability (SEP) expressions for the full-CSI SC, switch-and-examine combining (SEC), and SEC with postselection (SECps) schemes, considering M-ary phase-shift keying (MPSK) signaling over slow, flat, independent, and nonidentical Nakagami-m fading channels. It is to be noted that the derived SEP expressions are valid for integer values of fading severity parameter m. In addition, we also present the closed-form asymptotic SEP expressions for MPSK signaling to evaluate the diversity order. Concisely, from the numerical results, it is observed that the SECps scheme is able to offer the same performance as that of the full-CSI SC scheme. Furthermore, the SECps scheme outperforms the SEC scheme with more CSI.